Archaeological Collections of Count Keyserlingk and Other Lithuanian Landlords in the Courland Province Museum - Vasiliauskas, Ernestas (Archaeologia Lituana, 2016)
The archaeological finds (whose chronology covers the period from 4400/4200 BC to the 16th century AD) that were brought to the Courland Province Museum (1818–1939; Kurländischen Provinzial Museum, hereinafter the KPM) before 1916 (Fig. 1) from Kaunas Province (210 items from 12 localities, with another 2 find spots being mentioned (Fig. 2)) were mainly collected in the northern part of the country, in Samogitia, where landowners of German nationality had quite a few manors (Fig. 19, Tab. 1).It is from them that the first artefacts got to the KPM in 1835. In the period between 1840 to 1883, the finds came from old Lithuanian noblemen families (from Chlewiński via Ivan Loboiko, Benedikt Karp, and Tadeusz Dowgird).Since 1882, noblemen of German nationality, such as Count Keyserlingk, Barons von Behr, von Bistram, von Grotthuß, von Pfeilitzer-Franck, von der Ropp and others, got intensely involved in the search for antiquities and research of the past. The most active participants in the collection of artefacts and the organisation of research (already in the Courland Province) were Theodor ir Otto Keyserlingk (Malgūžė–Daunorava branch) (Figs. 3–4). The period of the finds getting into the KPM from Lithuania from 1828 to 1916 can be divided into 3 stages: Stage 1(1828–1835), Stage 2 (1840–1883), and Stage 3 (1882–1914). The participation of quite a few landowners from Lithuania in the activities of the Literature and Art Society in Courland (Kurländischen Gesellschaft für Literatur und Kunst, hereinafter the Society) and the Museum was limited to the provision of information or simply to membership (von der Ropp, von Bistram, von Löwenthal, and some of the Keyserlingk and von Pfeilitzer-Franck families), which meant paying anannual membership fee of 5 roubles.In most cases, the information accumulated in the KPM on some of the objects or on exclusive finds collected in them happens to be unique (cf. Adakavas (Fig. 11), Laukžemė, Lieporai, Moliūnai, Škilinpamūšis (Figs. 12–16), Viekšniai (Kaunas Province), Vecsaules Čapāni (Fig. 5), Jaunsvirlaukas Migaļas (Courland Province, etc.). Not long after that, in the late 19th century, the said archaeological materials were put into scientific circulation. In all cases, all the discovered finds since 1828 were more or less comprehensively overviewed in the Mitauische Zeitung newspaper (which in the period of 1811 to 1831 was published under the title Allgemeine deutsche Zeitung für Rusland), and since 1882, in an anual publication Sitzungsberichte der kurländischen Gesellschaft für Literatur und Kunst nebst Veröffentlichungen des kurländischen Provinzial-Museums of the Society. Moreover, a significant part of the said artefacts (those from Adakavas and Vecsaules Čapāni) were presented in the exhibition of the 10th Congress of Archaeology of the Russian Empire in Riga, in 1896.A great part of the finds referred to in the article were collected in the late 19th to the early 20th century during gravel mining works (Lieporai) or during earthworks in manors (Škilinpamūšis), or even during the construction of complex infrastructural objects, such as, e.g. channels (in Viekšniai in the first half of the 19th century); stone axes and coins came as choice finds from farmlands (Moliūnai, Laukžemė, and Žagarė). In almost all cases, the find spots were more or less precisely known, while in the case of Škilinpamūšis, the drawings of the artefacts made by Alfred von Behr in 1889 and the plan of the find spot situation survived (Figs. 15–16). Some of the collections accumulated by landlords can be characterised as collections proper (O. Keyserlingk’s collection of stone axes from Telšiai district) (Figs. 6–10, Table 2). Some of them, and primarily Keyserlingk, managed to avoid the problem of “scientific amateurism” by inviting specialists to the expeditions to cemeteries in Vecsaules Čapāni in 1886 and Jaunsvirlaukas Migaļas in 1895: the teacher of Jelgava Gymnazium, Carl Boy, or Secretary of Moscow Historical Museum, Wladimir Sisow, who were knowledgeable about the methodology of archeological excavations. Some others chose to carry out excavations by themselves (Adakavas, Paluknys). When it comes to the acquisition of the finds, one can see a fundamental difference: it was only in the second stage that the Lithuanian nobility carried out excavations in archaeological sites by themselves (Adakavas, Paluknys).In the expeditions to the North Lithuanian archaeological sites in the 70s-80s of the 19th century, artist Julius Döring (1818–1898) is known to have been actively assisted not only by representatives of the Karp family from Joniškėlis (in Panevėžys and Pasvalys districts in 1876), but also by A. von Behr (1848–1896) from Baltapamūšis, Eduard von der Ropp (1831–1892) from Raudonpamūšis (in the surveys of Ąžuolpamūšė Hillfort in 1882), Franz von Bistram (1854–1908) from Courland Grieze, Carl Keyserling (1809–1893) from Lithuanian Griežė (Heinrichswalde, Gaiķi, Griežė, Panevėžys branches) (in the surveys of the Griežė archaeological sites and the search for Apuolė there). Later, in the late 19th to the early 20th century, new names were included in the lists of the Society and Museum members: Friedrich von Grotthuß (Fig. 4) and Paul von Stempel. The KPM received several finds from them (Fig. 17).The involvement of landlords in the studies of the past of the north-central Lithuania can be accounted for by several reasons. First, the Baltic German landlords were closely related to Germany, from which the latest achievements in education, science, and culture would reach the region: in the present case, via the University of Tartu or directly, as quite a few of them were educated in Germany. In the case in question, besides Keyserlingk, Paul von Stempel, Benedikt, Joseph and Moritz Karp from Joniškėlis studied in the University of Tartu in 1880–1886, and Oskar Kurnatowski and some others, in 1853–1856; before that, they had studied in Jelgava Gymnazium which employed an active member of the Society J. Döring and others.
Keywords: archaeological collections; Alfred von Behr; Friedrich von Grotthuß; Theodor Keyserlingk; Ivan Loboiko; Mitau; Dorpat